Hounsfield Unit for Assessing Bone Mineral Density Distribution Within Cervical Vertebrae and Its Correlation With the Intervertebral Disc Degeneration - Liang, Xiao; Liu, Qingtao; Xu, Jiaxin; Ding, Wenyuan; Wang, Hui (Frontiers in Endocrinology, 2022)
Study Design: Retrospective radiological analysis. Objective: To assess bone mineral mass distribution within cervical vertebrae based on Hounsfield unit (HU) measurement, and explore its correlation with intervertebral disc degeneration. Method: Three hundred and twenty-four patients with degenerative cervical spine disease were retrospectively reviewed and divided into six groups according to age. HU measurement of the whole vertebrae from C3 through C7 was obtained, then HU measurement within upper and lower part of the vertebrae on sagittal plane were obtained from C3 through C7. Disc degeneration on MRI was graded from I to V using the Pfirrmann classification. Results: There was a significant difference in the HU value from C3 to C7 among Group II to Group Ⅵ, the HU value presented consistently decreasing trend from young patients to old patients. In C6 and C7 vertebrae, there were significant differences in HU values between upper and lower parts of the vertebrae. More importantly. In all groups, HU values were highest in the upper part of the C4 vertebrae and then gradually decreased towards C3 and C7. HU value of both upper and lower vertebrae presented decreasing trend along with the aggravation of the disc degeneration. Conclusion: HU values are not typically consistent throughout all levels of the cervical spine and the distribution within the vertebrae is not homogeneous. Decreased vertebral BMD and vertebral osteoporosis may trigger or exacerbate the adjacent intervertebral disc degeneration.